Ensuring Equal Opportunities in The Workspace When Organizing Working Hours - Olena Ye. Lutsenko; Olena H. Sereda; Sergii Prylypko; Oleksandr Patlachuk (UIN Sunan Gunung Djati, 2026)
This article reviews the question of whether the existing EU legal provision on working time is effective in guaranteeing substantive equality of opportunity in employment. It highlights a doctrinal gap in the EU labour law: whereas the Directive 2003/88/EC is officially intended to be a health and safety tool, the effect of this tool on equality (especially indirect discrimination and care responsibilities and disability accommodation) is still conceptually undeveloped and inconsistently applied. The research is characterized by a doctrinal legal approach, a mix of the analysis of EU primary and secondary law, and the Court of Justice of the EU case-law. The wider applicability of EU standards, such as to the Ukrainian labour law reform, is evaluated in a limited comparative perspective. The results show that formally neutral working-time practices, including long working hours, inflexible working schedules, and expansive derogations, may have disproportionately negative effects on women, caregivers, and persons with disabilities. The study reveals that the current framework has a weakness not in the lack of legal norms, but in its piecemeal interpretation of equality and ineffective enforcement procedures, especially in the area of working-time recording and opt-outs. The article contributes to the legal doctrine by conceptualizing the regulation of working time as an equality mechanism, not a technical or health-related problem. It calls for an equality-based review into the working-time law and suggests the reinforcement of enforcement, curtailing of derogations, and acknowledgement of access to flexible working arrangements as an element of employment equality.